Secondary recurrent miscarriage and sex of previous child - Raina, Deepali; Prashar, Nivedita; Sharma, Gopal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Secondary Recurrent Miscarriage (SRM) is defined as occurrence of three or more spontaneous consecutive abortions following the birth of one child. Mothers of boys often get immunized against male-specific minor histocompatibility (H-Y) antigens due to transfer of fetal cells into the maternal circulation. The birth of a boy is significantly more common than a girl prior to secondary recurrent miscarriage (SRM) and is known to be associated with a poorer chance of a subsequent live birth. Children born after Secondary Recurrent Miscarriage are more likely to be girls. Aberrant H-Y immunity may be a causal factor for SRM. Methods: The study was conducted over a period of one year from January 2012 to December 2012. All the women presenting with full term pregnancy and previous history of unexplained, three or more spontaneous consecutive abortions at 8 to 20 weeks gestation were taken as cases. Sex of the previous child was sought. The patients were followed till delivery and sex of the child born subsequently was also noted. Association of history of SRM to sex of the previous and present child was calculated by appropriates statistical methods. Results: A total of 34 patients with history of SRM were studied. 23 out of them had a previous male child and 11 had given birth to a female (p=0.004). The male: female sex ratio of children born prior and subsequent to SRM was 2.09 and 0.79 respectively. Conclusions: Study supports the hypothesis that aberrant maternal H-Y immune response may have a pathogenic role in SRM.